Different Heterotrimeric G Protein Dynamics for Wide-Range Chemotaxis in Eukaryotic Cells - Kamimura, Yoichiro; Ueda, Masahiro (Frontiers in Cell and Developmental Biology, 2021)
Chemotaxis describes directional motility along ambient chemical gradients and has important roles in human physiology and pathology. Typical chemotactic cells, such as neutrophils and Dictyostelium cells, can detect spatial differences in chemical gradients over a background concentration of a 105 scale. Studies of Dictyostelium cells have elucidated the molecular mechanisms of gradient sensing involving G protein coupled receptor (GPCR) signaling. GPCR transduces spatial information through its cognate heterotrimeric G protein as a guanine nucleotide change factor (GEF). More recently, studies have revealed unconventional regulation of heterotrimeric G protein in the gradient sensing. In this review, we explain how multiple mechanisms of GPCR signaling ensure the broad range sensing of chemical gradients in Dictyostelium cells as a model for eukaryotic chemotaxis.